2022
DOI: 10.1371/journal.pone.0275651
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lactate dehydrogenase predicts poor prognosis of acute ischemic stroke

Abstract: Background Lactate dehydrogenase (LDH) is associated with the prognosis of many diseases, but the relationship between LDH and the poor prognosis (recurrence and death) of acute ischemic stroke (AIS) has not been fully clarified. This study aimed to investigate the association between admission LDH level and poor prognosis in patients with AIS. Methods This retrospective study enrolled AIS patients treated in Taizhou Hospital of Zhejiang Province from July 2019 to December 2019. Poor prognosis included AIS r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, the relationship between LDH and poor IS outcomes remains unclear. In the current studies, some studies suggested that high LDH was associated with poor IS outcomes (Jin et al., 2022 ), including hemorrhagic transformation (Chen et al., 2023 ) and cognitive impairment (Xu et al., 2022 ). Conversely, it has also been suggested that LDH was not associated with adverse IS outcomes (Sharma et al., 2021 ).…”
Section: Introductionmentioning
confidence: 58%
“…However, the relationship between LDH and poor IS outcomes remains unclear. In the current studies, some studies suggested that high LDH was associated with poor IS outcomes (Jin et al., 2022 ), including hemorrhagic transformation (Chen et al., 2023 ) and cognitive impairment (Xu et al., 2022 ). Conversely, it has also been suggested that LDH was not associated with adverse IS outcomes (Sharma et al., 2021 ).…”
Section: Introductionmentioning
confidence: 58%
“…One report showed that LDH might be a risk predictor of poor prognosis and all-cause death of acute ischemic stroke, and the mortality rates at 3-month, 6-month, 12-month, and 18-month were 2.46%, 3.69%, 4.92%, and 5.33%, respectively. 16 It can also predict unfavorable outcomes after rt-PA thrombolysis is IS patients. 18 Regarding the clinical translation, removal of LDHB leads to an increase in symmetric neuronal terminal division.…”
Section: Discussionmentioning
confidence: 99%
“…LDHB is an enzyme involved in the conversion of lactate to pyruvate in the glycolytic pathway 14,15 . In the context of ischemic stroke, LDHB and lactate metabolism play a role in the response to the ischemic injury, and high LDH level indicates poor neurological outcome 16 . During ischemia, there is a reduction in oxygen and glucose supply to the affected area of the brain, which leads to a switch in cellular metabolism from aerobic metabolism (using oxygen) to anaerobic metabolism (without oxygen), resulting in an increase in lactate production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation